Strategy in increasing Consumer Loyalty - Ariffin, Muchammad - (Jurnal Ecoment Global, 2023)
The purpose of this study is to understand Strategy in increasing Consumer Loyalty. A Case Study of Indonesian Unilever Products. In particular, this study analyzes the relationshipbetween CSR, WOM and Company Reputation towards consumers' loyalty specially the products of Lifebuoy, Pepsodent, and Kecap Bango. Data was collected through a survey conducted among 110 respondents.Structural equation modeling was used to test the proposed hypothesis. The research model was tested using survey data analyzed by structural equation modelingof partial least squares. the implementation of CSR strategy shows that there is a significant influence of WOM and Company reputation on consumers' loyalty. On the other hand, CSR strategy has no significant influence the consumers' loyalty. Yet as CSR was carried out through the implementation of Word of mouth (WOM) and Company Reputation there is a significant correlation between CSR and the consumers' loyalty of Lifebuoy, Pepsodent, and Kecap Bango products. The use of data that is too small for each variable resulted in limited results. As well as the limited representation of all users and consumers of Unilever products in other cities. In addition, this study did not involve other companies that also use CSR strategies as a comparison. Keywords  :Corporate Social Responsibility (CSR), Word-of-mouth (WOM), Company Reputation, Consumers Loyalty, Social Company